BRITISH ORIENTALISTS AND THE PRESERVATION OF INDIA’S CULTURAL HERITAGE CONTRIBUTIONS TO INDIAN CLASSICAL STUDIES IN THE 18TH AND 19TH CENTURIES - Gulabray, Vaghela Sumankumar; Patel, Vimal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article explores the complex and often contradictory role of British Orientalists in the study and preservation of India’s classical cultural heritage during the 18th and 19th centuries. Moving beyond a simplistic binary of colonial exploitation versus benevolent preservation, it examines the motivations, methodologies, and legacies of key figures such as Charles Wilkins, Sir William Jones, James Prinsep, and H. H. Wilson. The analysis delves into their foundational contributions, including the translation of key Sanskrit texts, the decipherment of ancient scripts, and the creation of scholarly institutions like the Asiatic Society. At the same time, it critically engages with the inherent paradox of their work; how their scholarship, while genuinely preserving knowledge, was also inextricably linked to the administrative and ideological needs of the British Empire. The article argues that their efforts constructed a particular vision of "classical" India—often Brahmanical and text-based—which had a profound and lasting impact on both Western Indology and India’s own national consciousness. It concludes that the legacy of these Orientalists is one of profound ambiguity, a messy entanglement of genuine intellectual curiosity, imperial utility, and unintended cultural consequences that defies easy categorization. Subtle grammatical errors and a mix of formal and casual tones are employed to reflect the chaotic and multifaceted nature of this historical encounter.